1998
DOI: 10.1046/j.1471-4159.1998.71062313.x
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization and Complex Formation Between Prosaposin and Monosialoganglioside GM3 in Neural Cells

Abstract: Prosaposin, the precursor of saposins A, B, C, and D, was recently identified as a neurotrophic factor in vitro as well as in vivo. Its neurotrophic activity has been localized to a linear 12‐amino acid sequence located in the NH2‐terminal portion of the saposin C domain. In this study, we show the colocalization of prosaposin and ganglioside GM3 on NS20Y cell plasma membrane by scanning confocal microscopy. Also, TLC and western blot analyses showed that GM3 was specifically associated with prosaposin in immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 28 publications
4
30
0
Order By: Relevance
“…In a similar way, saposin C itself was shown to prevent apoptosis in prostate cancer cells [128]. These effects are consistent with the observations that prosaposin addition rescues neuroblastoma cells, primary hippocampal neurons [129], Schwann cells [125], and PC12 pheochromocytoma cells [119] from apoptosis induced by various agens. Neurotrophic, neuroregenerative and anti-apoptotic effects of prosaposin are apparently mediated by modification of signaling pathways and prosaposin was shown to be involved in ERK phosphorylation [130].…”
Section: Prosaposin Is a Potential Catalyst Of Ganglioside Shedding Asupporting
confidence: 77%
See 1 more Smart Citation
“…In a similar way, saposin C itself was shown to prevent apoptosis in prostate cancer cells [128]. These effects are consistent with the observations that prosaposin addition rescues neuroblastoma cells, primary hippocampal neurons [129], Schwann cells [125], and PC12 pheochromocytoma cells [119] from apoptosis induced by various agens. Neurotrophic, neuroregenerative and anti-apoptotic effects of prosaposin are apparently mediated by modification of signaling pathways and prosaposin was shown to be involved in ERK phosphorylation [130].…”
Section: Prosaposin Is a Potential Catalyst Of Ganglioside Shedding Asupporting
confidence: 77%
“…It has been suggested that its association with the cell membrane proceeds through the interaction with membrane gangliosides [118,119]. Prosaposin can also be found in many biological fluids such as seminal plasma, human milk, and cerebrospinal fluid (reviewed in [120]).…”
Section: Prosaposin Is a Potential Catalyst Of Ganglioside Shedding Amentioning
confidence: 99%
“…Recently, it has been reported that the HA1, HA3, and HA3b subcomponents of hemagglutinin, which is a component of the Clostridium botulinum progenitor toxin, use GM3 as a receptor (8,14). Misasi et al suggested that GM3-protein complexes are structural components of the prosaposin receptor involved in cell differentiation (25). We used flow cytometry with a monoclonal antibody to confirm that GM3 was expressed in U937 cells (data not shown).…”
Section: Discussionmentioning
confidence: 77%
“…3A, Western blot analysis of testis revealed several prosaposin isoforms: one of 65 kDa, two isoforms higher than 70 kDa, and one of 98 kDa in size. The different forms may correspond to different glycosylation states of prosaposin or to a prosaposin-lipid complex (10,21,39). Lower prosaposin levels were obvious in the testis of the Pro ⌬8neo homozygotes, while the Pro ⌬8 homozygotes had levels comparable to that of wild-type mice.…”
Section: Creating Mice Lacking Exon 8 Of Prosaposinmentioning
confidence: 98%